Parental Attachment, Anxiety, and Depression as Predictors of Internet Addiction Among Adolescents - Tesaviani Kusumastiwi; Warih Andan Puspitosari (Riviera Publishing, 2026)
Internet addiction has emerged as a growing behavioral concern among adolescents, driven by increased digital exposure and developmental vulnerability. Psychological factors such as anxiety and depression, along with relational factors including parental attachment, have been implicated in problematic internet use. A cross-sectional study was conducted among 87 high school students at senior high school in Yogyakarta, Indonesia. Internet addiction, parental attachment, anxiety, and depression were assessed using the Internet Addiction Diagnostic Questionnaire (KDAI), Inventory of Parent Attachment (IPA), and Hospital Anxiety and Depression Scale (HADS). Data were analyzed using Pearson correlation and multiple linear regression analyses. Parental attachment was negatively associated with internet addiction, whereas anxiety and depression demonstrated positive correlations. Anxiety showed the strongest association with internet addiction and remained the only significant independent predictor in the final regression model. Anxiety appears to play a central role in adolescents’ vulnerability to problematic internet use. These findings highlight the importance of early emotional screening, emotion regulation interventions, and supportive family environments in preventing maladaptive internet use among adolescents.